Goose astrovirus infection affects uric acid production and excretion in goslings - Wu, Wankun (Poult Sci, 2020)
In 2018, a new goose astrovirus (GAstrV) was reported in China, which causes 2 to 20% deaths in 4- to 16-day-old goslings causing great damages to the livestock industry. Gout is the typical feature of GAstrV infection in goslings. However, the mechanism of gout formation remains unclear. In the present study, 2-day-old goslings were infected intramuscularly with GAstrV for 14 D. One quarter of the infected goslings died, and typical gout pathological changes were found in the dead infected goslings. Pathological changes were observed in the morphology of the kidney and liver, such as degeneration, necrosis, and inflammatory cell infiltration. Accordingly, a high virus load was found in both organs. The serum level of uric acid in the inoculated goslings was higher, whereas no differences were found in levels of creatinine, calcium, and phosphorus. Moreover, the xanthine dehydrogenase (XOD) and adenosine deaminase (ADA) activities and the mRNA levels of xanthine dehydrogenase, adenosine deaminase, phosphoribosyl pyrophosphate amidotransferase, and phosphoribosyl pyrophosphate synthetase 1 in livers increased, wheres the multidrug resistance–associated protein 4 mRNA level and Na-K-ATPase activity in the kidneys decreased. These results showed that GAstrV infection could cause lesions on the liver and kidney and then increase the expression or activity of enzymes related to uric acid production in the liver and decrease renal excretion function, which contribute to hyperuricemia and gout formation.